Development of Volleyball Service Learning Model Through the Use of Sponge Ball Modification - Suryo Adi Nugroho; Sri Sumarni; Hartati Hartati; Iyakrus Iyakrus (Universitas PGRI Palembang, 2022)
The research objective in this research is whether the volleyball game using a sponge ball in valid, practical, and effective in the bottom serve learning model from the pre-test and post-test stages. This type of research is development research with research and development methods (R&D). Namely the potential and problems of data collection, product design, design validation, design revisions, product trials, product revivions, usage trials, product revisions, mass production. Data was collected using questionnaires obtained from expert evaluations (material experts and learning experts), small group trials (8 students) and large group trials (30 students), data in the from of product assessment results suggestions for product improvement and results. Filling out questionnaires by students. The data analysis technique used is descriptive percentage to reveal the affective, cognitive, and pyschomotor aspects of students after using the product. From the test results obtained expert evaluation data that is valid 98,75%practical learning expert 9.6% and material expert 9.8%small group trial psychomotor N-gain 0.89 cognitive N-gain 0.79 affective N-gain 0.73 large-group psychomotor trial N-gain 0.70, N-gain 0.59 affective N-gain 0.35. From the research above, it can be concluded that the volleyball bottom serve learning model through the use of this modified sponge of SMPK Brother Xaverius 1 Palembang.